2020
DOI: 10.3390/nu12020503
|View full text |Cite
|
Sign up to set email alerts
|

Association between Timing of Energy Intake and Insulin Sensitivity: A Cross-Sectional Study

Abstract: In addition to the caloric and macronutrient composition of meals, timing of energy consumption may be important for optimal glucose metabolism. Our goal was to examine whether the habitual timing of energy intake was associated with insulin sensitivity in healthy volunteers. Volunteers without diabetes aged 21–50 years completed a 3-day food diary and underwent an oral glucose tolerance test to estimate insulin sensitivity (n = 44). From the food diary, we calculated the proportions of the total energy and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…A 6-year prospective cohort study showed consuming more caloric intake at dinner had a 2-fold higher incidence of diabetes at follow-up [10]. One recent cross-sectional study [17] showed that a greater proportion of energy intake in the morning was positively related to insulin sensitivity estimated by Matsuda Index. Contrary to our anticipation, no negative relationship was observed between the "Morning dominant pattern" and insulin resistance in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 6-year prospective cohort study showed consuming more caloric intake at dinner had a 2-fold higher incidence of diabetes at follow-up [10]. One recent cross-sectional study [17] showed that a greater proportion of energy intake in the morning was positively related to insulin sensitivity estimated by Matsuda Index. Contrary to our anticipation, no negative relationship was observed between the "Morning dominant pattern" and insulin resistance in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 round included 7200 households within 360 communities (60 urban neighborhoods, 60 suburban neighborhoods, 60 towns, and 180 villages) across 15 diverse provinces (Heilongjiang, Liaoning, Shandong, Henan, Hubei, Hunan, Jiangsu, Guizhou, Guangxi, Shanxi, Yunnan, Zhejiang, Chongqing, Shanghai, and Beijing). The number of adult participants (age ≥ 18 years) was 17,193. After excluding participants who were, during the period of gestation or lactation (n = 218), diagnosed with hypertension, diabetes, myocardial infarction, apoplexy, or cancer (n = 3134), with missing important laboratory measurements (n = 4454), with missing demographic or lifestyle information (n = 527), with missing data on diet (60), and with extreme daily energy intake (higher than 5000 kcal/day or lower than 500 kcal/day) (n = 74); a total of 8726 participants were included in the analysis (Figure 1).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when we evaluated nutrient intake by meal, we found that the weight grain group had a significantly higher intake of saturated fat from dinner. According to previous findings, greater energy intake later in the day is significantly associated with lower insulin sensitivity [ 6 , 34 ] and night-time eating (25% or more of total energy consumed after 9 p.m.) is significantly associated with increased prevalence of metabolic syndrome [ 31 ]. Further investigations are needed to explore whether dietary quality or meal composition can enhance the positive effects of TRE on weight control and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Human TRE studies have largely been limited to observational studies [ 6 , 7 ]. Recently, several TRE intervention studies have been reported, although the findings are inconclusive.…”
Section: Introductionmentioning
confidence: 99%